Optimizing Islamic Bank Customer Satisfaction Through Mobile Banking And Internet Banking Services - Galih, Muchammad Damar; Setiawan, Firman (LPPM ISNJ Bengkalis, 2024)
This research aims to analyze the optimization of customer satisfaction through mobile and internet banking services at the Bank Syariah Indonesia (BSI) Jombang branch office. This research is field research using qualitative methods through a case study approach. Data was collected through in-depth interviews with six informants from BSI customers who actively use mobile and internet banking. The data analysis technique used is interactive analysis with several steps: data reduction, data presentation, and conclusions. The research results show that evaluating the user interface of mobile and internet banking services is necessary. Banks must improve the security of mobile and internet banking systems. Preparing for bank credibility and good integration between mobile and internet banking services, the bank needs to improve customer service to be more responsive and informative in mobile banking and internet banking services. This research can be a reference for future research and can be a reference for Islamic banking in optimizing online services, especially for BSI.